Tren Riset Global Realistic Mathematics Education (RME) Dalam Pembelajaran Matematika: Analisis Bibliometrik Menggunakan VOS Viewers - Nurhidayati, Siti; Purwoko, Riawan Yudi; Nugraheni, Puji; Suyitno (Jurnal PEKA (Pendidikan Matematika), 2026)
This study aims to analyze global research trends in Realistic Mathematics Education (RME) in mathematics learning during the 2021-2025 period and to map dominant themes and scholarly collaboration patterns. A quantitative bibliometric approach was employed using international publications retrieved from Dimensions AI and analyzed with VOSviewer to visualize co-authorship, co-citation, and keyword co-occurrence networks. The results indicate a declining trend in RME-related publications over the past five years, although the topic remains pedagogically relevant. AIP Conference Proceedings emerged as the most productive publisher, while the Journal of Physics: Conference Series recorded the highest number of citations. Author analysis identified Armiati as the most productive researcher, and keyword mapping revealed the dominance of themes related to instructional design, realistic contexts, and effectiveness, with recent research trends focusing on systematic studies and the implementation of RME at the elementary school level. Overall, the findings provide a comprehensive overview of global research trends in Realistic Mathematics Education (RME) and offer valuable insights for guiding future research and supporting innovation in mathematics education.